Depression, anxiety and suicidal behaviour among college students: Comparisons pre-COVID-19 and during the pandemic - McLafferty, Margaret; Brown, Natasha; McHugh, Rachel; Ward, Caoimhe; Stevenson, Ailis; McBride, Louise; Brady, John; Bjourson, Anthony J.; O'Neill, Siobhan M.; Walsh, Colum P.; Murray, Elaine K. (Psychiatry Research Communications, 2021)
BACKGROUND: Many students struggle with psychological problems during their college years. These problems may be even more apparent during the COVID-19 pandemic with the accompanying restrictions and transition to an online learning environment, but few longitudinal studies have been conducted to date. The aim of this study was to compare symptoms of depression, anxiety and suicidality prior to and during the pandemic, and identify stressors. METHODS: This study was conducted among students attending Ulster University, Northern Ireland (NI) and LYIT, Republic of Ireland (ROI), as part of the World Mental Health International College Student Initiative (WMH-ICS). Data was collected from first year students in September 2019. The completed response rate was 25.22% (NI) and 41.9% (ROI) in relation to the number of first-year students registered. A follow up study was conducted in Autumn 2020, with 884 students fully completing the online survey in both years, equating to just under half of those who completed initially. RESULTS: High levels of mental health problems were found in year 1, especially in the ROI. Levels of depression increased significantly in year 2, particularly among students in NI, however, levels of anxiety decreased. No significant variations were found for suicidal behaviour. Several stressors were revealed, including increased social isolation, and worrying about loved ones. LIMITATIONS: The findings may not be generalised to other student populations. CONCLUSIONS: This study reveals variation in symptoms of depression and anxiety since the onset of the pandemic. In particular, the large increase in students with depression is of concern.
Keywords: Anxiety; College students; Depression; Pandemic; Suicidality